"Brincar-vem" : a criança surda na educação infantil e o despertar das mãos - Côrtes, Diolira Maria (2012)
This study had the objective of analyzing the conditions which are available for deaf children to learn Libras (Brazilian Sign Language) in a Municipal Center of Child Education, which is a reference for the education of such children, in the city of Vitoria, Espírito Santo. The theory used was historic- cultural. The studies of Vigotski and Bakhtin were used as reference, and emphasis was given to language and to the role the other has in the human constitution. As a methodological option, the qualitative research was chosen, which was developed by means of an ethnic case study. For the collection of empirical material, the study made use of participative observation, daily record, video-recording, interviews with the participants in the research, and analysis of school enrollment registrations. The organization and analysis of data had the support of the micro genetics, a methodological option adopted by some studies that have a historic-cultural perspective as reference, in order to understand the conditions in which three children, who were in the initial stage, learned Libras. The selected analysis elements were the mediation process established by adults and other children in relation to the deaf children, as well as the learning signs shown by them in the classroom and during the specialized educational attention. The analysis indicated that the conditions for learning Libras still constitute a challenge for some children who experience a restrict context for interaction in Libras due to, among other reasons, the lack of knowledge in Libras among adults and children, and to the fact that the bilingual team do not have the necessary number of professional to work with them in different places. The study also indicates the need to find the best way when considering the specificity of deaf children in child education. Keeping in mind that individuals learn language while they are emerged in the flow of verbal communication, the study points out the necessity of having deaf professional working directly with these children, which would contribute to the formation of their identity, to their learning and to their development, as the legislation defines.